Tides in Three Enclosed Basins: The Baltic, Black, and Caspian Seas - Medvedev, Igor P.; Rabinovich, Alexander B.; Kulikov, Evgueni A. (Frontiers in Marine Science, 2016)
Tides are the main type of sea level variability in the world ocean. However, oceanic tides penetrate weakly, or do not penetrate at all, into enclosed basins such as the Baltic, Black and Caspian seas. Consequently, only directly forced tides are formed in these basins. Long observation time series (up to 123 years in the Baltic Sea and 38 years in the Black and Caspian seas) at numerous stations were used to precisely estimate tidal constituents. High-resolution spectra revealed fine structure of discrete peaks at tidal frequencies. The diurnal radiational constituent S1 (1 cpd), apparently associated with breeze winds, was found to play an important role in general tidal dynamics in these seas. Harmonic analysis of tides for individual yearly series with consecutive vector averaging over the entire observational period was applied to estimate mean amplitudes and phases of tidal constituents. Our findings indicate that the formation and predominance of diurnal or semidiurnal tides in these seas appears to depend on the frequency-selective properties of the basins. Thus, in the Baltic Sea with fundamental modal period of about 27 h, diurnal tides dominate in the major eastern gulfs. In the Black Sea resonant amplification of semidiurnal tides is observed in the northwestern part. The predominance of semidiurnal tides in the Caspian Sea has also probably a resonant nature. Maximum tidal heights estimated for a 100-year period are 23 cm in the Baltic Sea, 18 cm in the Black Sea and 21 cm in the southern Caspian Sea.